Patient-focused drug development and real-world study - Haiyin Hu; Hui Wang; Lin Ang; Menglong Shi; Xiaolei Wu; Chenyao Zhang; Mei Han; Shigang Liu; Kai Li; Junhua Zhang; Zhaochen Ji (Integrative Medicine Research)
Patient-focused drug development (PFDD) is an important direction in medical research and is highly important for the development of medicine. In recent years, PFDD and real-world study (RWS), both of which have advantages, have attracted much interest. The aim of this review was to promote research method innovation and optimize clinical research design and implementation. In this review, clinical trials using PFDD and RWS were compared in terms of objectives, population, intervention, comparator, outcome (PICO) elements, research team members, data acquisition, and key research points and also the feasibility and significance of the “patient-focused RWS” research model were clarified. PFDD emphasizes that patients’ needs, willingness and satisfaction, should be considered throughout the entire research process and that patient experience data should be collected during study development and drug use. RWS emphasizes the facticity of the research implementation environment and the breadth of patient sources, focusing on the problems of the extrapolation of study results, the clinical localization, and patient applicability of the target drug. However, there is a connection between the above factors. Clinical trials using PFDD and RWS have both shown benefits for patients. Combining PFDD concepts and RWS methods to carry out new research will maximize the benefits for patients. A study model that combines the PFDD concept with RWS to facilitate drug development and dissemination can be popularized and applied in various research areas. This review may lead to innovative research methods and provide new ideas for future research.